Pengaruh Kualitas, Kepuasan, Dan Kepercayaan Terhadap Loyalitas Pelanggan Paket Internet Simpati (Studi Pada Mahasiswa Universitas Potensi Utama) - Leni Nadiya Lubis; Austin Alexander Parhusip (Jurnal Bintang Manajemen, 2023)
Customer loyalty is a customer's commitment to a brand, store or supplier based on a very positive nature. And customer loyalty consists of several variables, namely: quality, satisfaction and trust. This study aims to determine and analyze the effect of quality, satisfaction, and trust on customer loyalty with internet packages of sympathy (study on major potential university students) as of April 1, 2022. This study used 152 respondents as research samples. By using a random sampling technique using the Slovin formula and processing data using SPSS Version 26. Based on the results of the analysis, it can be seen that the three variables used in this study proved to have a positive and significant influence on customer loyalty. And through the results of this test, it can be seen that the test value of the Adjusted R Square coefficient of determination is 0.502 which means that 50.2% of customer loyalty there are factors obtained, namely quality, satisfaction, and trust. While the remaining 100% - 50.2% = 49.8% is explained by other variables such as price, promotion, and brand image which are not examined in this study.